Impact of cigarette taxes and prices in Latin America tobacco smoking prevalence: A systematic review - Ana Leticia Mores; Maria Eduarda Pérez-de-Oliveira; Ana Gabriela Costa Normando; Leticia Rodrigues-Oliveira; Gustavo Nader Marta; Renata Ferrarotto; Thaís Bianca Brandão; Alan Roger Santos-Silva; Ana Carolina Prado-Ribeiro (Oral Oncology Reports)
The present systematic review (SR) aimed to analyze the impact of cigarette taxes and prices on the prevalence of tobacco smoking in Latin America countries. The methods of this SR were previously established and registered in PROSPERO (CRD42022319407) and was reported according to the PRISMA checklist. The searches were made in 5 databases (PubMed/MEDLINE, Scopus, Embase, Web of Science and LILACS) in addition to the grey literature, without limitation of year, and published in English, Spanish or Portuguese. Studies which analyzed cigarette taxes and prices on tobacco smoking prevalence in Latin America were eligible for inclusion. The study selection was conducted in two phases by two independently reviewers. Seven observational studies conducted in Brazil, Mexico and Colombia were included in the qualitative analysis. The risk of bias (RoB) of each study was assessed using the Joanna Briggs Institute checklist. All studies found that an increase in excise taxes of cigarette led to an increase in the retail price. Four studies (57.1 %) reported that increasing cigarette taxes and prices was effective to decrease the prevalence of tobacco smoking. The included studies were graded as having a low (57.1 %) or moderate (42.8 %) RoB. The use of cigarette taxes and prices measures are effective tools to reduce the prevalence of tobacco smoking. However, it is vital the development of further research on this topic in other countries of Latin America since the included studies were performed only in Brazil, Colombia and Mexico.